The origin of heresy: a history of discourse in Second Temple Judaism and early Christianity - Royalty, Robert M. (Routledge studies in religion, 2013)
The origin of heresy -- The rhetoric of difference in Israel -- Reform and revolution in the Roman Empire: John the Baptist and the disciples of Jesus -- Paul and the rhetoric of difference -- The Christian Gospels as narratives of exclusion -- Policing the boundaries: the politics of heresiology -- The politics of orthodoxy -- Conclusions